Efficacy and Toxicity of Combined Inhibition of EGFR and VEGF in Patients With Advanced Non–small Cell Lung Cancer Harboring Activating EGFR Mutations: A Systematic Review and Meta-analysis. (20th March 2023) - Deluce, Jasna; Maj, David; Verma, Saurav; Breadner, Daniel; Boldt, Gabriel; Raphael, Jacques
Abstract : Dual inhibition of epidermal growth factor receptor (EGFR) and vascular endothelial growth factor (VEGF) pathways have demonstrated promising results for treatment of advanced non–small cell lung cancer. We conducted a systematic review and meta-analysis to assess the efficacy and toxicity of the combined treatment with EGFR tyrosine kinase inhibitors (TKIs) and VEGF blockade for patients with advanced non–small cell lung cancer harboring activating EGFR mutations, in comparison to EGFR TKIs alone. The electronic databases were searched for relevant randomized trials between 2000 and 2022. The primary endpoints were overall survival (OS) and progression-free survival. Secondary endpoints included objective response rate (ORR), disease control rate, and grade ≥3 adverse events (AEs). The pooled hazard ratios (HR) and odds ratios were meta-analyzed using the generic inverse variance and the Mantel-Haenszel methods. A total of 1528 patients from 8 trials were evaluated for analyses. The combination treatment decreased the risk of disease progression by 37% (HR=0.63; 95% CI, 0.56 to 0.72) but had no added benefit on OS compared with EGFR inhibition alone (HR=0.90; 95% CI, 0.76 to 1.05). There was no significant difference in objective response rate or disease control rate between treatments. There was a significantly increased number of AEs reported in the dual treatment arm (odds ratio=3.02; 95% CI, 1.71 to 5.31), with proteinuria and hypertension being the most significantly increased AEs. This meta-analysis suggests combined inhibition of EGFR and VEGF pathways significantly improves progression-free survival, with no OS benefit, and increases AEs. Mature OS data are needed along with results from more trials exploring this strategy with third-generation EGFR TKIs to strengthen these results.